N′-[(1E)-(4–Fluorophenyl)methylidene]adamantane-1-carbohydrazide, C18H21FN2O - Al-Wahaibi Lamya H.; Abdelbaky Mohammed S. M.; Garcia-Granda Santiago; Reiss Guido J.; Tiekink Edward R. T.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures)
C18H21FN2O, triclinic, P1‾$P\overline{1}$ (no. 2), a = 10.6377(5) Å, b = 14.4869(7) Å, c = 21.0557(13) Å, α = 98.583(5)°, β = 91.979(4)°, γ = 90.101(4)°, V = 3206.5(3) Å3, Z = 8, Rgt(F) = 0.0815, wRref(F2) = 0.1930, T = 172 K.